2004
DOI: 10.1103/physrevlett.93.263401
|View full text |Cite
|
Sign up to set email alerts
|

First Laser-Controlled Antihydrogen Production

Abstract: Lasers are used for the first time to control the production of antihydrogen (H ). Sequential, resonant charge exchange collisions are involved in a method that is very different than the only other method used so far-producing slow H during positron cooling of antiprotons in a nested Penning trap. Two attractive features are that the laser frequencies determine the H binding energy, and that the production of extremely cold H should be possible in principle-likely close to what is needed for confinement in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(106 citation statements)
references
References 21 publications
0
103
1
1
Order By: Relevance
“…This is in stark contrast to the rather high H temperature observed when using the nested-well technique pioneered by ATRAP and ATHE-NA [24,25]. Our proposed technique is conceptually similar to a charge exchange technique based on Rydberg cesium [26] which has been successfully demonstrated by ATRAP [27].…”
Section: Antihydrogen Recombination and Beam Formationcontrasting
confidence: 42%
“…This is in stark contrast to the rather high H temperature observed when using the nested-well technique pioneered by ATRAP and ATHE-NA [24,25]. Our proposed technique is conceptually similar to a charge exchange technique based on Rydberg cesium [26] which has been successfully demonstrated by ATRAP [27].…”
Section: Antihydrogen Recombination and Beam Formationcontrasting
confidence: 42%
“…11,12 The production of low energy antihydrogen using a method that requires positronium has also been demonstrated. 13 Antihydrogen research may ultimately provide experimental tests of CPT (charge conjugation, parity, time reversal) and gravity symmetries. [14][15][16][17][18][19][20] There exist numerous conflicting issues associated with using nested Penning traps to produce antiatoms with sufficiently low energies and also in sufficient numbers for conducting high precision CPT and gravity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…ATRAP demonstrated that H could be produce by a two-step, laser-controlled charge exchange process [57]. This process has possible advantages over the three-body formation in a nested Penning trap [23] in that the lasers control the excitation state of the H that is formed, and by offering H kinetic energies as cold (or hot) as the p from which the H forms.…”
Section: Building On 100 Times More H Atoms Produced By Laser-controlmentioning
confidence: 99%